Factors Preventing the Actualisation of Ummah Wasaá¹a in the Republic of Tatarstan, Russia - Rafikov, Ildus (IIUM Journal of Religion and Civilisational Studies, 2018)
This article discusses the traits of the concept of ummah wasaá¹a, its historical roots, and its modern application to the Muslim community of the Republic of Tatarstan, Russia. It identifies the main factors preventing the actualisation of the â€œjustly balancedâ€ ummah standards in Tatarstan. The study was conducted using the textual analysis methodology with reference to the pertinent literature in English and Russian. The main finding of this article is that the establishment of ummah wasaá¹a among the Muslims in Tatarstan is challenging at the present time due to the Tatarsâ€™ identity crisis, disunity among the various factions of Muslims at various levels, the pressures coming from the law enforcement agencies, and the absence of a strong umbrella organisation.